Effective Conduction of Laboratory Courses in Online Learning using Virtual Lab - Patil, Ashwini; Mane, Dadaso; Patil, Savita; Homkar, Akshay; Jadhav, Priyanka (Journal of Engineering Education Transformations, 2025)
In the Covid 19 pandemic, education shifted from offline to online, impacting a lot of technical education. The online theory courses were conducted effectively, but there were a lot of problems the faculty faced in conducting laboratory courses. This problem includes an ineffective demonstration of lab experiments, difficulty in time management, monitoring, and assessment, inability to tackle the issues of various students’ learning styles, and unavailability of a common platform for online lab conduction. In technical education, the lab course plays a vital role. We found that a virtual laboratory is the best solution to address these issues. Many virtual labs are available for programming courses but need a customized Virtual lab for core courses. In this paper, we have carried out 16 surveys through Google forms to get inputs/feedback from faculties and students to get difficulties in online lab conduction and how we can make the best use of virtual labs online to conduct the lab experiment online mode. We designed and created the virtual laboratory for the Computer Networks Lab course with various learning materials, including theory, simulation videos, pre-test & post-test, and the procedure to conduct the lab experiment, which benefited the students. The implemented virtual lab found more effective. We found the significant impact on the result of CN Lab after using the customized virtual lab for CN Lab course.